PENGARUH BANGSA PEJANTAN DAN INTERVAL DEPOSISI SEMEN TERHADAP KEBERHASILAN INSEMINASI BUATAN PADA AYAM - Irastuti, Irastuti (JSTT, 2011)
Abstract: This research has been carried out in the stable, the research department of Animal Husbandry Faculty of Agriculture, University of Tadulako from December to April 2011. research purposes to study the stud and cement deposition appropriate intervals, in the period of fertility and produce fertile sperm and egg hatchability of high post-IB, in the hens reproductive tract, through the observation of a number of eggs produced by a certain time.The study design used was Completely Randomized Design (CRD) 3 x 3 factorial pattern, with a combination of two treatment factors (A, B). The treatments tested consisted of three (3) the stud (free-range chicken, chicken arabic, and chicken bangkok) and 3 (three) intervals of semen deposition (day 3, day 5 and day 7) on fertility of spermatozoa and the fertile period spermatozoa and egg hatchability. Each treatment was repeated as many as 3 (three) times. The results showed that treatment of the males give real effect (P <0.05) on fertility, sperm fertile period and hatchability of eggs. The treatment interval of deposition of cement did not provide significant effect (P <0.05) on fertility and sperm fertile period, but the effect of cement deposisi interval significantly(P <0.05) on the hatchability of eggs, the two factor interactions do not occur. Key words: Effect of males, Interval of Semen Deposition dan Artificial Inseminatioan.